Cochlear Implants in Adults: Effects of Age and Duration of Deafness on Speech Recognition. Issue 9 (October 2016) - Beyea, Jason A.; McMullen, Kyle P.; Harris, Michael S.; Houston, Derek M.; Martin, Jennifer M.; Bolster, Virginia A.; Adunka, Oliver F.; Moberly, Aaron C.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Unexplained outcome variability exists among adults with cochlear implants (CIs). Two significant predictors are age and duration of deafness, with older patients and those with longer durations of deafness generally demonstrating poorer speech recognition. However, these factors are often highly correlated. Thus, it is unclear whether poorer outcomes should be attributed primarily to age-related declines or to the experience of auditory deprivation. Our aim was to examine the effects of aging and duration of hearing loss on outcomes for postlingually deaf adults with CIs. Study Design: Retrospective review of adults who received CIs from 1983 to 2014. Setting: Tertiary adult CI program. Patients: Sixty-four adult patients with postlingual hearing loss beginning after age 12 years, full electrode insertion, normal cochlear anatomy, and availability of postoperative outcome measures. Intervention: Cochlear implantation with 12 months or greater of device use. Main Outcome Measures: Postoperative pure-tone averages (0.5, 1, 2, and 3 kHz) and recognition of words in sentences (Hearing in Noise Test and AzBio). Results: Age at postoperative testing had a negative partial correlation with AzBio scores, when controlling for duration of deafness, whereas duration of deafness had a positive partial correlation with AzBio scores, when controlling for age. No other effects were identified. Conclusion: Older age at testing was associated with poorer recognition of words in difficult sentences, suggesting that cognitive aging may negatively impact CI outcomes. Further studies are needed to examine how a long duration of auditory deprivation affects CI outcomes.